THE EFFECT OF WEBSITE QUALITYAND ELECTRONIC WORD OF MOUTH ON TRUST TO ENCOURAGE PRODUCT PURCHASE DECISION THROUGH BERRY BENKA (CASE STUDY: BERRY BENKA CONSUMER) - Mirza, Muhammad; Djumarno; Permana, Dudi (Dinasti International Journal of Digital Business Management, 2021)
ThisXstudy aims to analyze the influence of website quality, Electronic Word of Mouth, Trust,and purchasingXdecisions. The object of this study was berrybenka consumers, and the number of sempel determined was 210 respondents using a calculation method based on heir formula multiplied by 5. XPurposiveXsamplingXmethod, data collection method using questionnaire, and data analysis usingXPartialXLeast Square (PLS). The results of the study are known that Website Quality affects purchasingXdecisions, ElectronicXWord of Mouth affects purchasingXdecisions, XTrust influences purchasing decisions, TrustXinfluences purchasing decisions, XWebsite QualityXaffects Trust, Electronic WordXofXMouth affectsTrust, Trust plays a role in mediating Website Qualityto consumer decisions, Trust plays a role in mediating Electronic Word of Mouth to consumer decisions.